Integrated Three-Dimensional Carbon Nanopolyhedron/Metal Sulfides: An Efficient Electrocatalyst Toward Oxygen Reduction Reaction - Yang, Yi-Wen; Song, Bing-Ye (Frontiers in Energy Research, 2021)
The carbon-based materials hybridized with metal sulfides have gained growing attention as catalytic materials for oxygen reduction reaction (ORR) due to their synergy effect in terms of richer structural features and higher electrochemical activities. Here, a series of Zn/Co/Fe-based metal-organic frameworks as the precursors are synthesized, which can be adopted as the efficient ORR catalysts through a sulfuration-calcination treatment. The effects of precursor composition, heteroatom doping and pyrolysis temperature on the structure and electrochemical performance of the catalysts are discussed in detail. It is found that well-grown carbon nanotubes (CNTs) on the surface of graphitic carbon matrix are formed under the synergy effect of trimetallic-based species during pyrolysis. Benefiting from the three-dimensional unique structure with appropriate dopants and high porosity, the catalyst derived from the optimized Zn/Co/Fe-MOFs achieves a half-wave potential of 0.87 V in alkaline medium for ORR, which is comparable to commercial electrocatalysts. In addition, an outstanding ORR durability of proposed catalyst in alkaline media is also demonstrated. This work highlights the potential to rationally design and fabricate high-performance ORR catalysts for commercialization.